Indoor air pollution - Kavuncuoğlu, Duygu; Koşan, Zahide (Journal of Surgery and Medicine, 2019)
Clean air is one of the essential preconditions of life. Approximately 4.3 million people die due to indoor air pollution every year. The majority of these deaths are due to stroke (34%), ischemic heart disease (26%), and chronic obstructive pulmonary disease (22%). The principal indoor air pollutant particulate materials are carbon monoxide, tobacco smoke, formaldehyde and volatile organic compounds, nitrogen dioxide, asbestos, radon, and biological pollutants (micro-organisms and allergens). The prevention of indoor air pollution and use of clean energy sources must be regarded as an opportunity to improve health, particularly that of mothers and children, reduce poverty, and achieve environmental sustainability.